(untitled) (Universal International Scientific Journal, 2026)
This article discusses the biological nature of temperament, which is considered the fundamental basis of personality psychology, and its relationship with character. The article analyzes temperament as an innate property of the human nervous system, that is, as a "biological foundation" that determines the level of emotional excitability and activity of a person. The study scientifically substantiates the unchanging nature of temperament and the transformation of character in the process of upbringing, as well as the harmony of these two factors in the development of a person